IMPLEMENTASI METODE PEMBELAJARAN BRAINSTORMING UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 30 MAKASSAR - Alhidayat; Syahid, Akhmad; Ahmad; Subaedah; Syahrul, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve student learning outcomes in Islamic Religious Education through the application of the Mind Mapping-based Brainstorming method in class VIII.8 of SMP Negeri 30 Makassar. This study was motivated by the low learning outcomes of students, as indicated by the average pre-cycle score of 68, still below the Minimum Completion Criteria (KKM) of 75, as well as the low student activity during the learning process. The type of research used is Classroom Action Research (CAR) with the Kemmis and McTaggart model consisting of the planning, action implementation, observation, and reflection stages. The study was conducted in two cycles with 30 students of class VIII.8 as research subjects. Data collection techniques include observation, learning outcome tests, and documentation. Data were analyzed quantitatively through calculating the average and percentage of learning completion and qualitatively through observations of teacher and student activities. The results showed that the application of the Mind Mapping-based Brainstorming method was able to improve the process and learning outcomes of students. Teacher activity increased from 75% in cycle I to 84% in cycle II, while student activity increased from 66% to 84%. The completion of learning outcomes also increased, namely from 53.33% in cycle I to 86.67% in cycle II. In addition, students showed an increase in active discussion, courage to express opinions, ability to work together, and skills in compiling mind maps. Based on these results, it can be concluded that the Mind Mapping-based Brainstorming method is effective in improving student learning outcomes in Islamic Religious Education subjects in class VIII.8 SMP Negeri 30 Makassar and is worthy of being used as an alternative learning that is innovative, active, and student-centered.